Mobile Learning Based Learning Using Etno Edu Games to Improve Students' Critical Thinking and Cognitive Abilities on IPAS Subjects in Grade IV Elementary School - Rahayu, Widia Indah; Leksono, Suroso Mukti; Nulhakim, Lukman (Postgraduate, University of Mataram, 2024)
Basically, elementary school age students are still very interested in playing or games. The principle of playing while learning can create a pleasant atmosphere for students in learning. In playing, children have the freedom to channel and express what their hearts desire. An atmosphere like this will encourage students to be more enthusiastic and have more critical thinking skills. Anticipating science learning which seems difficult, so that mobile learning based learning methods using ethno edugames can be applied. The formulation of the problem to be researched is: How is mobile learning based learning using ethno edugames in class IV elementary school? How can mobile learning-based learning using ethno edu games improve students' critical thinking skills in grade IV elementary school? How can mobile learning-based learning using ethno edugames improve students' cognitive outcomes on force material in class IV elementary school? The research method used is quasi-experimental quantitative research with a pretest-posttest control group design. The total population is 96 students and the sample size is 64 students. With one class for the experimental group and one class for the control group. The conclusions from the results of this research are: there is an influence of mobile learning based learning using ethno edugames on improving students' critical thinking skills in class IV elementary school. There is an influence of mobile learning based learning using ethno edu games on improving students' cognitive abilities in class IV elementary school. There is an influence of mobile learning based learning using ethno edugames on increasing the critical thinking and cognitive abilities of students in class IV elementary school.